2012
DOI: 10.1186/1471-2431-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Poor food and nutrient intake among Indigenous and non-Indigenous rural Australian children

Abstract: BackgroundThe purpose of this study was to describe the food and nutrient intake of a population of rural Australian children particularly Indigenous children. Participants were aged 10 to 12 years, and living in areas of relative socio-economic disadvantage on the north coast of New South Wales.MethodsIn this descriptive cross-sectional study 215 children with a mean age of 11.30 (SD 0.04) years (including 82 Indigenous children and 93 boys) completed three 24-hour food recalls (including 1 weekend day), over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
11
35
2
Order By: Relevance
“…29,30 A study of food and nutrient intake in rural Australia reported that energy-dense nutrient poor food consumption, such as sugary drinks, are commonly consumed, and this is particularly prevalent in Indigenous children. 31 To reduce the burden of dental caries, and its progression, it is recommended that sugars should make up 2-3% of energy intake. 32 Recently, there has been a significant push to tax sugary beverages, similar to the tobacco tax, as a strategy to reduce consumption.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A study of food and nutrient intake in rural Australia reported that energy-dense nutrient poor food consumption, such as sugary drinks, are commonly consumed, and this is particularly prevalent in Indigenous children. 31 To reduce the burden of dental caries, and its progression, it is recommended that sugars should make up 2-3% of energy intake. 32 Recently, there has been a significant push to tax sugary beverages, similar to the tobacco tax, as a strategy to reduce consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The OCPP was a randomized clinical trial aimed at assessing the effect of 4 mg versus 0.4 mg folic acid, taken daily during preconception and the first trimester of pregnancy, on oral cleft recurrence among women who themselves have or have had a child with an oral cleft without other birth defects [17, 21, 22]. The women included in our study were enrolled into the OCPP between January 29, 2004 and April 27, 2005, which covers the period before and after initiating the fortification program in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Among children ages 4 to 15 years in the 1999-2002 National Health and Nutrition Examination Survey (NHANES), 8.2% had parent-reported ADHD. 1 The National Survey of Children's Health found that 10.1% of children in the 2007 survey 2 and 11% of children in the 2011-12 survey had parent reported ADHD. 3 Children with ADHD have difficulty maintaining focus and controlling their behavior; some exhibit hyperactivity.…”
mentioning
confidence: 99%